2005
DOI: 10.1097/00000542-200501000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Halothane and Isoflurane on Hyperexcitability of Spinal Dorsal Horn Neurons after Incision in the Rat

Abstract: The results demonstrate that administration of halothane and isoflurane does not attenuate development of hyperexcitability of SDH neurons despite the fact that excitation and spontaneous activity during and after the incision were greatly suppressed by administration of halothane and isoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Neuronal responses to a surgical incision were suppressed by 1.0 MAC of halothane and isoflurane to 47% and 66%, respectively, relative to 0 MAC in spinaltransected decerebrated rats (7). Neuronal responses to heat (51°C) were suppressed by 1.0 MAC of halothane to Figure 3A plotting initial response versus anesthetic concentration.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Neuronal responses to a surgical incision were suppressed by 1.0 MAC of halothane and isoflurane to 47% and 66%, respectively, relative to 0 MAC in spinaltransected decerebrated rats (7). Neuronal responses to heat (51°C) were suppressed by 1.0 MAC of halothane to Figure 3A plotting initial response versus anesthetic concentration.…”
Section: Discussionmentioning
confidence: 93%
“…Such an interpretation of differential action is limited however, because halothane and isoflurane's action on neuronal responses over the 0 -0.8 MAC range are incompletely known. Whereas halothane depresses dorsal horn spinal neurons in this lower range, there are limited similar data for isoflurane (5)(6)(7). For example, depression of dorsal horn neurons by either anesthetic at small (0 -0.8 MAC) concentrations may provide a state of reduced sensorimotor transmission upon which further increases in anesthetic concentration (0.8 -1.2 MAC) can effectively block noxious stimulus-evoked movement.…”
mentioning
confidence: 99%
“…When the values of two successive TFL were very close with a difference within 0.5 s, anesthesia was regarded as stable and the average from the two was defined as ''basal latency''. Usually, 15-20 min was enough for reaching a stable measurement from our experience and those reported by others (Bing et al, 1991;Cuellar et al, 2004;Kawamata et al, 2005). The ''test latency'' was the same as that described in Section 2.2.…”
Section: Induction Period and Maintenance Period Of Anesthesiamentioning
confidence: 88%
“…Similar findings have been reported for halothane and isoflurane regarding the lack of effectiveness of these gases to reduce neuronal hyperexcitability in the dorsal horn after surgery in rats. 22 Other studies reported differential effects of halogenous anesthetics on windup phenomena and neuronal excitability in the dorsal horn 36 or the effects of halogenous anesthetics on wide-dynamic range neuronal activity in the dorsal horn. 37 One limitation of this work stems from a pharmacological viewpoint, that it would have been justified to have evaluated the effects of higher concentrations of sevoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…8,[18][19][20] Halogenated anesthetics have in vitro anti-NMDA properties. [21][22][23][24] Other studies have shown that halogenated anesthetics induce hyperalgesia when administered at very low concentrations 25,26 and even decrease morphine analgesic effects. 25,27 However, in the context of current clinical practice, it is unresolved as to whether or not inhaled anesthetics elicit residual effects on postoperative hyperalgesia.…”
Section: Résumémentioning
confidence: 99%